Pembinaan Dan Penguatan Life Skill Santri Dengan Program Muhadharah (Public Speaking) Di Pesantren Ma Swasta Zakiyun Najah Sei Rampah Kabupaten Serdang Bedagai - Syahrendi, Muhammad; Barus, Jusua; Novianti, Winda (STAI Tebing Tinggi Deli, 2024)
The development and reinforcement of life skills among students are crucial aspects of their character and competency growth. This study aims to evaluate the effectiveness of the Muhadharah (public speaking) program in enhancing public speaking skills and other life skills at Pesantren MA Swasta Zakiyu Najah in Sei Rampah, Serdang Bedagai Regency. The Muhadharah program is designed to train students in effective speaking skills, material mastery, and confidence in communication. The research employs a qualitative approach with data analysis through observations, interviews, and document studies. The findings indicate that the Muhadharah program successfully improved students' public speaking skills, enhanced their communication abilities, and positively impacted other life skills such as leadership, empathy, and adaptability. The program also contributed to the development of students' mental resilience and self-confidence in social and academic settings. The conclusion of this study is that the Muhadharah program is an effective strategy for life skill development in pesantren, providing positive outcomes for students' personal growth. It is recommended that this program be continuously developed and tailored to meet students' needs to maximize its benefits within the pesantren educational context.